Indonesian versus English versions of Pesona Indonesia commercial: Investigating internationalization in translation - Adinda V. Clarasati, Encik Irindayanti, Retno W. Setyaningsih, (Opción, 2019)
This study aims to reveal the internationalization of Indonesian and English versions of Pesona Indonesia commercial published in 2017. In analyzing the data, the writers synthesized the theory of instruktionen, which consist of intralinguistic (linguistic aspects) and extralinguistic (non-linguistic situational context) X proposed by Katharina Reiss. As a result, this commercial consist of intralinguistic and extralinguistic criteria which are different. Moreover, both of the findings of intralinguistic and extralinguistic criteria are affected by internationalization. In conclusion, internationalization is applied in the English version of Pesona Indonesia commercial since it uses the English language.